Tunisia Economic Monitor, Fall 2020 : Rebuilding the Potential of Tunisian Firms - World Bank (World Bank, Washington, DC, 2021)
Tunisia is expecting a sharper decline in growth than most of its regional peers, having entered the COVID-19 (coronavirus) crisis whilst already experiencing slow growth and rising debt levels. After an expected 9.2 percent contraction in 2020, growth is temporarily expected to accelerate to 5.8 percent in 2021 as the pandemic’s effects begin to abate, before returning to a more subdued growth trajectory at around 2 percent by 2022, reflecting pre-existing structural weaknesses. With this, some of the past gains in job creation and poverty reduction will be lost as unemployment edges up and the share of the population vulnerable to falling into poverty increases. In this difficult context, restoring the credibility of the macroeconomic framework is a critical next step for Tunisia to successfully navigate its way through this crisis and lay the foundation for a more durable recovery in growth. The special focus in this edition of the Tunisia Economic Monitor draws on the recently published enterprise survey for Tunisia to discuss the latest evidence on firm performance and present priorities for a growing and more productive private sector.